Differentiation of porcine induced pluripotent stem cells (Pipscs) into neural progenitor cells (npcs) - Machado, Lucas Simões; Recchia, Kaiana; Pieri, Naira Caroline Godoy; Botigelli, Ramon Cesar [UNESP]; de Castro, Raquel Vasconcelos Guimarães; Cruz, Jéssica Brunhara; Pessôa, Laís Vicari de Figueiredo; Bressan, Fabiana Fernandes (MyJove, 2021)
iPSC-derived neurons are attractive in vitro models to study neurogenesis and early phenotypic changes in mental illness, mainly when most animal models used in pre-clinical research, such as rodents, are not able to meet the criteria to translate the findings to the clinic. Non-human primates, canines, and porcine are considered more adequate models for biomedical research and drug development purposes, mainly due to their physiological, genetic, and anatomical similarities to humans. The swine model has gained particular interest in translational neuroscience, enabling safety and allotransplantation testing. Herein the generation of porcine iPSCs is described along with its further differentiation into neural progenitor cells (NPCs). The generated cells expressed NPC markers Nestin and GFAP, confirmed by RT-qPCR, and were positive for Nestin, b-Tubulin III, and Vimentin by immunofluorescence. These results show the evidence for the generation of NPC-like cells after in vitro induction with chemical inhibitors from a large animal model, an interesting and adequate model for regenerative and translational medicine research.